Germacrone inhibits early stages of influenza virus infection - Liao, Qingjiao; Qian, Zhengxu; Liu, Rui; An, Liwei; Chen, Xulin (Antiviral research, 2013)
•Germacrone is a major component of the essential oil extracted from Rhizoma Curcuma.•Germacrone has antiviral effect against several influenza viruses dose-dependently.•The early stages of the viral life cycle are affected by germacrone.•Germacrone showed an effective protection of mice from lethal infection of influenza. Highly pathogenic influenza viruses pose a serious public health threat to humans. Although vaccines are available, antivirals are needed to efficiently control disease progression and virus transmission due to the emergence of drug-resistant viral strains. In this study, germacrone, which is a major component of the essential oils extracted from Rhizoma Curcuma, was found to inhibit influenza virus replication. Germacrone showed antiviral activity against the H1N1 and H3N2 influenza A viruses and the influenza B virus in a dose-dependent manner. The viral protein expression, RNA synthesis and the production of infectious progeny viruses were decreased both in MDCK and A549 cells treated with germacrone. In a time-of-addition study, germacrone was found to exhibit an inhibitory effect on both the attachment/entry step and the early stages of the viral replication cycle. Germacrone also exhibited an effective protection of mice from lethal infection and reduced the virus titres in the lung. Furthermore, the combination of germacrone and oseltamivir exhibited an additive effect on the inhibition of influenza virus infection, both in vitro and in vivo. Our results suggest that germacrone may have the potential to be developed as a therapeutic agent alone or in combination with other agents for the treatment of influenza virus infection.